2023
DOI: 10.2147/idr.s407620
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram for Predicting Delayed Viral Shedding in Non-Severe SARS-CoV-2 Omicron Infection

Abstract: The Omicron variant of SARS-CoV-2 has emerged as a significant global concern, characterized by its rapid transmission and resistance to existing treatments and vaccines. However, the specific hematological and biochemical factors that may impact the clearance of Omicron variant infection remain unclear. The present study aimed to identify easily accessible laboratory markers that are associated with prolonged virus shedding in non-severe patients with COVID-19 caused by the Omicron variant. Patients and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Therefore, platelets, as a prominent component of blood, may participate in the elimination of the Omicron variant or its components. Supporting this possibility, a recent report suggests a correlation between platelet counts and Omicron clearance efficiency ( 53 ). Additionally, it is plausible to suggest that platelets, and megakaryocytes ( 23 ), may contribute to the dissemination of the virus, which first affects the lungs and then spreads via the blood stream, infecting various organs and tissues.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, platelets, as a prominent component of blood, may participate in the elimination of the Omicron variant or its components. Supporting this possibility, a recent report suggests a correlation between platelet counts and Omicron clearance efficiency ( 53 ). Additionally, it is plausible to suggest that platelets, and megakaryocytes ( 23 ), may contribute to the dissemination of the virus, which first affects the lungs and then spreads via the blood stream, infecting various organs and tissues.…”
Section: Discussionmentioning
confidence: 89%
“… Gui et al (2023) built a nomogram involving four individual and clinical characteristics (older age, more comorbidities, incomplete vaccination course, and lack of antiviral therapy) to accurately predict the risk of 14-day PCR-based negative conversion failure among Omicron cases. Yu et al (2023) reported that six factors (age, C-reactive protein, platelet count, leukocyte count, lymphocyte count, and eosinophil count) were associated with delayed viral shedding time in non-severe SARS-CoV-2 Omicron cases. These studies focused on the influence of demographic and clinical characteristics on NCT.…”
Section: Introductionmentioning
confidence: 99%